2005
DOI: 10.1016/j.ecoleng.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine in soils, sludges, biogases and atmospheric implications—a review

Abstract: This is a review of previously published and unpublished results of research into the occurrence of phosphine (PH 3 ) in the environment in the form of matrix bound phosphine in soils, aquatic sediments and sludges (range ng kg −1 to g kg −1 ), free phosphine in formed biogases (range ng m −3 to g m −3 ) and in the atmosphere (range pg m −3 to ng m −3 ). The reviewed data support the hypothesis of the existence of a small gaseous link in the phosphorus cycle, which could become important over the long term.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 24 publications
1
69
0
Order By: Relevance
“…Under the reduced conditions typically prevalent in wetlands, Dèvai et al (1988) reported that oxidised P compounds were reduced to phosphine, which was subsequently emitted to the atmosphere at a rate of 1.7 g P m −2 per year (a −1 ). To date there has been very little research into this process, which requires further investigation in order to determine if it is signifi cant in terms of quantity of P exported, and the fate of gaseous P. Glindemann et al (2005) have provided a useful review of research into the evolution of phosphine in a range of sediments.…”
Section: Hydrologymentioning
confidence: 99%
“…Under the reduced conditions typically prevalent in wetlands, Dèvai et al (1988) reported that oxidised P compounds were reduced to phosphine, which was subsequently emitted to the atmosphere at a rate of 1.7 g P m −2 per year (a −1 ). To date there has been very little research into this process, which requires further investigation in order to determine if it is signifi cant in terms of quantity of P exported, and the fate of gaseous P. Glindemann et al (2005) have provided a useful review of research into the evolution of phosphine in a range of sediments.…”
Section: Hydrologymentioning
confidence: 99%
“…As an aside about phosphine (PH 3 ), we note that trace amounts of phosphine are produced by some anaerobic ecologies on Earth (Glindemann et al 2005). It is controversial whether the microorganisms in these environments are making PH 3 or whether the bacteria are making acid that is attacking environmental iron that contains traces of phosphide and this attack is making the phosphine gas (Roels & Verstraete 2001).…”
Section: Type I Biosignature Gas Overviewmentioning
confidence: 99%
“…Atmospheric phosphorus mainly originates from aeolian dust, sea spray, and combustion . Gaseous forms of phosphorus are scarce, and their importance for atmospheric processes is unknown (Glindemann et al, 2005).…”
Section: Phosphorus Cyclementioning
confidence: 99%